Hubungan Indeks Masa Tubuh dengan Kadar Trigliserida Pada Penenun Tradisional di Tenganan Karangasem - I G.A. Sri Dhyanaputri (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2019)
Background Body mass index is the one of the marker of nutritional status related to obesity. Obesity is a multifactorial disease that can lead to an increase in triglycerides. This situation is one of the causes of cardiovascular disease. Objective This study aims to determine the relationship between body mass index in the levels of trigliycerides in weavers in Tenganan Village Karangasem. Methods Designed as study correlation study. The study was done to 26 respondents that were chosen by saturated sampling method. Data of body mass index were measured by anthropometric measurements and data of triglycerides level measured by using a dialab autolyser. The Results showed that 50,00% participants got obesity and 42,31% participants had increased triglycerides level, which six participants (23,08%) got a high limit and five participants (19,23%) in the high category. Based on the product moment test, a score is significant correlation between body mass index with triglycerides (p: 0,000) (α: 0,05). It was Concluded there is a relationship between body mass index with triglycerides level of weavers at Tenganan Village Karangasem.Keywords: body mass index, obesity, triglycerides